2017
DOI: 10.1177/0162353217717032
|View full text |Cite
|
Sign up to set email alerts
|

Why Would You Say Goodnight to the Moon? Response of Young Intellectually Gifted Children to Lower and Higher Order Questions During Storybook Reading

Abstract: Research into the effect of questions asked during storybook reading in preschool settings has rarely investigated questions that elicit higher order thinking. In the current study, Blank et al.'s Four Levels of Abstraction were used to code teacher questions and child responses from 177 individual storybook reading sessions with eight intellectually gifted 3-and 4-year-old children. The aim was to investigate the level of cognitive response gifted preschoolers made to lower and higher order questions during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Strategies that use higher order thinking skills can be used to help 2E children develop and demonstrate their advanced cognitive thought processes (Walsh, Bowes, & Sweller, 2017). In a study that captured twice-exceptional learner’s perceptions of effective strategies, higher order thinking skills was rated as one of the “most beneficial” learning strategies by participants (Willard-Holt et al, 2013, p. 257).…”
Section: Higher Level Questioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies that use higher order thinking skills can be used to help 2E children develop and demonstrate their advanced cognitive thought processes (Walsh, Bowes, & Sweller, 2017). In a study that captured twice-exceptional learner’s perceptions of effective strategies, higher order thinking skills was rated as one of the “most beneficial” learning strategies by participants (Willard-Holt et al, 2013, p. 257).…”
Section: Higher Level Questioningmentioning
confidence: 99%
“…Higher level questioning (HLQ) strategies are often recommended to stimulate and challenge gifted students and students who demonstrate gifted potential, especially young intellectually gifted children (McCollister & Sayler, 2010; Robinson, Shore, & Enersen 2007; Shaunessy, 2000; Walsh et al, 2017; Walsh & Kemp, 2013). Research has found that questioning strategies, particularly those based on the higher levels of Bloom’s revised taxonomy (i.e., Analyzing, Evaluating, Creating), aid in the development of critical thinking skills, creativity, higher order thinking skills (Daniels, 1997; Gallagher, 1985; Shaunessy, 2000), and more complex verbal responses for young gifted children (Walsh et al, 2017). Unfortunately, lower level questions, many of which simply require students to recall basic factual information, are most prominent in school settings (Gallagher, 1985; Siraj-Blatchford & Manni, 2008; Wimer, Ridenour, Thomas, & Place, 2001).…”
Section: Higher Level Questioningmentioning
confidence: 99%
See 1 more Smart Citation
“…At the ES level, it is clear that they can begin to learn to evaluate a person's attitude towards the environment. This is certainly a positive thing considering the ability to evaluate is one part of HOTS that needs to be trained (Gunduz et al, 2016;Madhuri, Kantamreddi, & Goteti, 2012;Walsh, Bowes, & Sweller, 2017). In Table 5, it is clear that on the 5th indicator about making a hypothesis, ES students have the highest score compared to the other levels.…”
Section: Discussionmentioning
confidence: 98%
“…Hertzog, Klein and Katz (1999) conducted a one-year project approach with 3-4 and 5-6-year-old children and found that the project approach supported the questioning skills. Walsh, Bowes and Sweller (2017) have shown that children improve their questioning skills through storytelling. Adelson and Carpenter (2011), on the other hand, found that 8 gifted students have high-level skills in the study which is related to the high-level thinking with 43 storybooks.…”
Section: Discussionmentioning
confidence: 99%